A conceptually novel construction of the 6a-hydroxypterocarpan skeleton – Synthesis of (±)-variabilin. Issue 22 (15th November 2017) - Ciesielski, Philipp; Metz, Peter
Graphical abstract: Abstract: A new access to the 6a-hydroxypterocarpan variabilin was established. Key step of this concise total synthesis is a challenging cyclization of a haloketone via halogen–metal exchange and subsequent intramolecular addition to the carbonyl function.